Lymph node dissection in digestive neoplasms - Fernández, Ricardo; Henderson, Eduardo; Rodríguez, Gustavo; Vivas, Carlos; Canessa, César; Pignanesi, Daniel; Plazzotta, Cecilia (Cirugía del Uruguay, 2003)
We want to express our gratitude to the authorities of the 51st Uruguayan Congress of Surgery, for the designation with which we have been honored. During the Symposium the topic will be discussed of the "Lymph node dissection in neoplasms digestive ". The objective of the same is, in a first instance, an update of the subject, to then present partial casuistry of our middle and finally try to draw conclusions about to the current state of our reality in surgery oncological.